Asymmetric effects of hydroclimate extremes on eastern US tree growth: Implications on current demographic shifts and climate variability - Justin T. Maxwell; Tsun Fung Au; Steven A. Kannenberg; Grant L. Harley; Matthew P. Dannenberg; Darren L. Ficklin; Scott M. Robeson; Macarena Férriz; Michael C. Benson; Benjamin R. Lockwood; Kimberly A. Novick; Richard P. Phillips; et al. (Global Change Biology, 2024)
Forests around the world are experiencing changes due to climate variability and human land use. How these changes interact and influence the vulnerability of forests are not well understood. In the eastern United States, well‐documented anthropogenic disturbances and land‐use decisions, such as logging and fire suppression, have influenced forest species assemblages, leading to a demographic shift from forests dominated by xeric species to those dominated by mesic species. Contemporarily, the climate has changed and is expected to continue to warm and produce higher evaporative demand, imposing stronger drought stress on forest communities. Here, we use an extensive network of tree‐ring records from common hardwood species across ~100 sites and ~1300 trees in the eastern United States to examine the magnitude of growth response to both wet and dry climate extremes. We find that growth reductions during drought exceed the positive growth response to pluvials. Mesic species such as Liriodendron tulipifera and Acer saccharum , which are becoming more dominant, are more sensitive to drought than more xeric species, such as oaks ( Quercus ) and hickory ( Carya ), especially at moderate and extreme drought intensities. Although more extreme droughts produce a larger annual growth reduction, mild droughts resulted in the largest cumulative growth decreases due to their higher frequency. When using global climate model projections, all scenarios show drought frequency increasing substantially (3–9 times more likely) by 2100. Thus, the ongoing demographic shift toward more mesic species in the eastern United States combined with drier conditions results in larger drought‐induced growth declines, suggesting that drought will have an even larger impact on aboveground carbon uptake in the future in the eastern United States.

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

Application of Physiologically Based Absorption Modeling to Formulation Development of a Low Solubility, Low Permeability Weak Base: Mechanistic Investigation of Food Effect - Hefei Zhang; Binfeng Xia; Jennifer Sheng; Tycho Heimbach; Tsu-Han Lin; Handan He; Yanfeng Wang; Steven Novick; Ann Comfort (AAPS PharmSciTech, 2014)

A Two One-Sided Parametric Tolerance Interval Test for Control of Delivered Dose Uniformity. Part 1—Characterization of FDA Proposed Test - Steven Novick; David Christopher; Monisha Dey; Svetlana Lyapustina; Michael Golden; Stefan Leiner; Bruce Wyka; Hans-Joachim Delzeit; Chris Novak; Gregory Larner (AAPS PharmSciTech, 2009)

A Two One-Sided Parametric Tolerance Interval Test for Control of Delivered Dose Uniformity—Part 3—Investigation of Robustness to Deviations from Normality - Steven Novick; David Christopher; Monisha Dey; Svetlana Lyapustina; Michael Golden; Stefan Leiner; Bruce Wyka; Hans-Joachim Delzeit; Chris Novak; Gregory Larner (AAPS PharmSciTech, 2009)